Stories of Indonesian Workers in Australia: A Needs Analysis of Communicative Competence in Multicultural Settings - Hasyim Kurniawan (Universitas Gadjah Mada, 2026)
Opportunities for Indonesians to work in Australia are growing. However, there is limited information on how to adequately prepare them for effective English communication and adaptation in a multicultural and multilingual workplace environment. Revisiting the expanded framework of communicative competence, including linguistic, strategic, interactional, multidialectal, and metacultural competencies, this study explores how Indonesian migrant workers navigate real-world communication in Australia. Using narrative inquiry, this needs analysis (NA) draws from in-depth interviews with six university-educated Indonesians under Working Holiday (WHV) and Dependent Visas (DV), all with at least six months of work experience across industries such as hospitality, cleaning, retail, and factory work. Thematic analysis revealed key gaps in job-specific vocabulary (e.g., tools, workplace areas, food terms), listening challenges with diverse English accents (Indian, Chinese, Australian), and difficulties with interactional norms and self-advocacy in intercultural settings. Participants also reflected on how prior grammar-focused instruction left them unprepared for spontaneous, task-oriented exchanges. Findings also show that in real workplace interactions, participants often drew on strategic competence (e.g., clarification, circumlocution) and metacultural competence (e.g., explaining religious practices, responding to dietary taboos) more than on grammatical accuracy. Nonetheless, some contrasting views suggested that grammatical competence can still play a key role in certain jobs, especially those involving customer service or opportunities for job advancement. These findings challenge the general English curriculum in Indonesia and underscore the importance of English for Specific Purposes (ESP) that aligns closely with actual workplace demands.